Motion Assessment Application Design Development Android based Artistic Gymnastics - M. Ikhsan Rizaldi Nasution; Imran Akhmad; Rahma, Rahma Dewi (UNIB Press, 2024)
This study is to measure the feasibility of developing an android-based artistic movement assessment application design. The purpose of this study is to produce an android-based artistic gymnastics assessment application product that can be used for students of SMA XI Private Maitreyawira in assessing floor gymnastics exams. Trial on students who take part in learning activities at SMA XI Private Maitreyawira. This study uses the development of Research & Development (R&D) from. Based on the results of the feasibility assessment by material experts, the material aspect obtained a percentage score (92%), the application aspect obtained a percentage score (88%). The results of the feasibility assessment by media experts on the material aspect obtained a percentage score (94%), on the video aspect obtained a percentage score (95%), and on the application aspect obtained a percentage score (96%). The results of the feasibility assessment by PJOK teachers in the use of an android-based artistic movement assessment application obtained a percentage score (95%). Student learning outcomes on floor gymnastics material obtained a percentage score (91%), with an average score of 90.6. Based on the results of this android-based application design development research, it can be concluded that the assessment instrument is feasible to use in assessing floor gymnastics for class XI SMA Private Maitreyawira.